Mechanical and electromagnetic vibrations and waves - Bécherrawy, Tamer (Hoboken, NJ : John Wiley & Sons, Inc., 2012)
Annotation Dealing with vibrations and waves, this text aims to provide understanding of the basic principles and methods of analysing various physical phenomena. The content includes the general properties of propagation, a detailed study of mechanical (elastic and acoustic) and electromagnetic waves, propagation, attenuation, dispersion, reflection, interference and diffraction of waves. It features chapters on the effect of motion of sources and observers (both classical and relativistic), emission of electromagnetic waves, standing and guided waves and a final chapter on de Broglie waves constitutes an introduction to quantum mechanics.
Free oscillations -- Superposition of harmonic oscillations, Fourier analysis -- Forced oscillations -- Propagation in infinite media -- Mechanical waves -- Electromagnetic waves -- Reflection and refraction of waves -- Interference and diffraction -- Standing waves and guided waves -- Answers to the problems -- Appendices. Mathematical review -- Units in physics -- Some physical constants -- Further reading -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Electromagnetic fields -- Mathematical models; Electromagnetic waves -- Mathematical models; Electrodynamics -- Mathematical models; Oscillations -- Mathematical models; Engineering mathematics; Electromagnetic Waves; Electromagnetic Fields; Electrodynamics; Oscillations; Engineering Mathematics; Electrodynamics -- Mathematical models; Electromagnetic fields -- Mathematical models; Electromagnetic waves -- Mathematical models; Engineering mathematics; Oscillations -- Mathematical models; Electronic books